Extensive expertise in endocrinology: UK stance on adult GH replacement: the economist vs the endocrinologist - Shalet, S M (European journal of endocrinology, 2013)
In the UK, through the use of a forced economic model, endocrinologists are in the curious position of offering GH replacement to some patients with severe GH deficiency (GHD) but withholding it from other patients with even more severe GHD. This approach is counter-intuitive to endocrine practice in treating endocrine deficiency states. For all other endocrine deficiencies, one would opt for treating those with the most severe biochemical evidence of deficiency first. If this endocrine approach was applied to adult GH replacement in an era of rationing, one would start with the GHD patients with a pathologically low IGF1 level. Given that the prevalence of subnormal IGF1 levels in a GHD population is age-dependent, this would result in GH replacement being offered to more young adult onset (AO) GHD and childhood onset GHD adults, and less often to middle-aged and elderly AO GHD adults. This in itself has the added advantage that the skeletal benefits appear more real in the former cohort of patients.